Road network modeling of Jalan Tanjung Lumpur-Pekan and federal road 3 using EMME/3 - Aishah, Shahid-Din (2009)
Urban transportation planning is the process that leads to decisions on transportation policies and programs. The transportation planning process relies on travel demand forecasting, which involves predicting the impacts that various policies and programs will have on travel in the urban area. The forecasting process also provides detailed information, such as traffic volumes, bus patronage, and turning movements, to be used by engineers and planners in designs. EMME/3 is an urban transportation planning system that helps transportation planners and traffic engineers to model the travel demand. All the data related to urban activities, network data, model definitions and travel demand can be unified as the EMME/3 database. The accuracy of modeling system is how we performed in constructing the computerized network representation. For this study, this road network is modeled by using origin destination (OD) table based on gravity model. The gravity model illustrates the macroscopic relationships between places for example like homes and workplaces or in other words, the gravity model assumes that the trips produced at an origin and attracted to a destination are directly proportional to the total trip productions at the origin and the total attractions at the destination. Therefore this is an vital scenario to the authorities in prediction for the future traffic forecast in managing the future development.